Avifauna do Parque Estadual Juquery, São Paulo, como subsídio para a elaboração do Plano de Manejo - Santos, Matheus de Moraes dos (Universidade Federal de São Carlos, 2024)
The maintenance of Brazilian protected areas (UCs) relies on the management plan, which is an essential tool for defining the responsibilities and objectives of the UC, based on its biotic and abiotic characteristics. Birds are one of the best-known biological groups and their diversity reflects the variety of specializations, niche occupations, and ecological functions within ecosystems. In this study, a list of birds was compiled for the Juquery State Park, Franco da Rocha (JSP), SP, Brazil, which still lacks a management plan. The methodology was divided into a preliminary survey, carried out through citizen science websites and previous scientific publications. Subsequently, field efforts were undertaken to identify and validate the bird species currently present in JSP. These efforts resulted in 315 species which, after screening, culminated in the official list containing 264 species divided into 58 families and 23 orders. Passerines exhibited the greatest diversity, with a predominance of the families Thraupidae (34) and Tyrannidae (32), followed by Trochilidae (13) from the order Apodiformes. Twenty species are endemic to the Atlantic Forest biome, two are endemic to the Cerrado and one is typical of the Pampas. Based on the diversity of species detected in the field, the presence of threatened species, and the richness of migratory species, the JSP is defined as a fully-protected area according to the Brazilian law (“Unidade de Conservação de Proteção Integral”), and has proven to be an important area for the conservation of bird biodiversity in the metropolitan region of São Paulo. The avifauna composition is more than 50% similar to that of the the Cantareira State Park, which is a part of the mosaic of protected areas in São Paulo metropolitan area. Therefore, JSP is confirmed as a significant site for the conservation of bird biodiversity in the metropolitan region of São Paulo.
Avifauna of Juquery State Park, São Paulo, as subsidy for the preparation of the Management Plan
Keywords: Juquery; UC; Aves; Biodiversidade; Plano de manejo; Protected areas; Birds; Biodiversity; Management plan; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ZOOLOGIA; CIENCIAS BIOLOGICAS